THE IMPACT OF ARTIFICIAL SWEETENERS ON INSULIN RESISTANCE IN WOMEN WITH POLYCYSTIC OVARY SYNDROME (PCOS): A LITERATURE REVIEW - Michał Pogoda; Dominika Pietrzyk; Gabriela Furtak; Maria Łagódka; Katarzyna Zając; Bartosz Oder; Wiktor Daniszewski; Wiktoria Knobelsdorf; Wojciech Karchut; Bartłomiej Gałuszka (International Journal of Innovative Technologies in Social Science, 2025)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders, affecting up to 20% of women of reproductive age worldwide. A central feature of PCOS is insulin resistance (IR), which contributes to hyperandrogenism and worsens reproductive and metabolic symptoms. Given the growing prevalence of PCOS and the widespread use of artificial sweeteners (AS) as sugar substitutes, their potential influence on metabolic health in this population warrants closer examination.Aim: This review aims to assess the current literature on the effects of artificial sweeteners on insulin resistance in women with PCOS, to determine whether their use may exacerbate or mitigate metabolic dysfunctions associated with the syndrome.Methods: A narrative literature review was conducted using the most recent and relevant publications. The review focuses on the biochemical and physiological mechanisms of AS, including their effect on cephalic phase insulin secretion, pancreatic beta-cell response, gut microbiota composition, and hormonal signalling related to glucose metabolism and insulin sensitivity.Results: The impact of AS on metabolic health appears to be heterogeneous and dose-dependent. Some sweeteners, such as saccharin and sucralose, may influence insulin secretion and gut microbiota in ways that contribute to glucose intolerance and IR. However, evidence is inconsistent and varies by sweetener type and study model. In PCOS patients, where IR is a core pathological feature, the use of certain artificial sweeteners may potentially worsen metabolic outcomes.Conclusion: Artificial sweeteners are not metabolically inert and may affect insulin resistance in women with PCOS. Further research is needed to evaluate individual AS compounds and their long-term metabolic effects in this population, in order to inform dietary recommendations and optimize treatment outcomes.